2022
DOI: 10.3390/jfmk7010011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Accumulated Workloads in Collegiate Women’s Soccer: A Comparison of Starters and Reserves

Abstract: Research quantifying the unique workload demands of starters and reserves in training and match settings throughout a season in collegiate soccer is limited. Purpose: The purpose of the current study is to compare accumulated workloads between starters and reserves in collegiate soccer. Methods: Twenty-two NCAA Division III female soccer athletes (height: 1.67 ± 0.05 m; body mass: 65.42 ± 6.33 kg; fat-free mass: 48.99 ± 3.81 kg; body fat %: 25.22 ± 4.78%) were equipped with wearable global positioning systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Unlike A vg W, A cc W considers total volume and intensity accrued throughout an entire season to reflect the total work completed. Although initial reports on the accumulated physical loading experience of athletes highlight potential utility as a method of chronic workload quantification (11,25,35), its application in research has been limited to the sport of soccer.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike A vg W, A cc W considers total volume and intensity accrued throughout an entire season to reflect the total work completed. Although initial reports on the accumulated physical loading experience of athletes highlight potential utility as a method of chronic workload quantification (11,25,35), its application in research has been limited to the sport of soccer.…”
Section: Introductionmentioning
confidence: 99%
“…While great strides have been made in understanding the physical requirements of elite level soccer in recent decades, there is a lack of inquiry surrounding match play in collegiate soccer in the US. Preliminary work has revealed the physical demand of men's 3,4 and women's 5,6 collegiate soccer, with both practice and competition contributing to high accumulated workloads over the course of a competitive season. Interestingly, it has been suggested the format of collegiate soccer in the US may also present distinct challenges not seen in other competition levels.…”
Section: Introductionmentioning
confidence: 99%
“…The TRIMP model was originally designed to work using training heart rate (HR) and time, but more recent studies have shown that it could work using RPE and time, resulting in the session RPE (sRPE) [ 6 , 7 , 8 , 9 ]. More recent studies have suggested that it could be understood using responses during the warm-up for subsequent exercise bouts [ 10 ], questionnaires [ 11 ], HR variability (HRV) [ 12 , 13 , 14 ], or training intensity distribution [ 15 , 16 , 17 ]. In any case, the process of monitoring training using any tool appears to be a useful method of evaluating the exerciser (athlete fitness rehabilitation) and optimizing exercise prescription [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were carried out in collegiate soccer players [ 12 , 13 , 14 ]. Aiming to compare accumulated workloads between starters and reserves in collegiate soccer, Jagim et al [ 12 ] reported a greater distance covered by starters throughout the season, resulting in almost double the training load compared to reserves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation